2019
DOI: 10.1371/journal.pmed.1002892
|View full text |Cite
|
Sign up to set email alerts
|

Impact on child acute malnutrition of integrating small-quantity lipid-based nutrient supplements into community-level screening for acute malnutrition: A cluster-randomized controlled trial in Mali

Abstract: Background Community-based management of acute malnutrition (CMAM) has been widely adopted to treat childhood acute malnutrition (AM), but its effectiveness in program settings is often limited by implementation constraints, low screening coverage, and poor treatment uptake and adherence. This study addresses the problem of low screening coverage by testing the impact of distributing small-quantity lipid-based nutrient supplements (SQ-LNSs) at monthly screenings held by community health volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(80 citation statements)
references
References 43 publications
0
80
0
Order By: Relevance
“…We identified 15 trials that met our inclusion criteria, 14 of which provided individual participant data and are included in this analysis (Figure 1, Table 1) (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Investigators for one trial were unable to participate (49).…”
Section: Literature Search and Trial Characteristicsmentioning
confidence: 99%
“…We identified 15 trials that met our inclusion criteria, 14 of which provided individual participant data and are included in this analysis (Figure 1, Table 1) (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Investigators for one trial were unable to participate (49).…”
Section: Literature Search and Trial Characteristicsmentioning
confidence: 99%
“…Taken together, the findings from our study and its companion study in Mali [8] highlight the trade-offs of using community- versus health center–based services for the delivery of AM services. Choosing the CNS as the intervention platform for strengthening AM screening offered several advantages.…”
Section: Discussionmentioning
confidence: 52%
“…However, impact studies using SQ-LNS in similar populations of similar age in Burkina Faso showed mixed effects of SQ-LNS on AM indicators; one study (included in the meta-analysis cited above) found a 4.8 pp (36%) reduction of wasting when SQ-LNS was combined with treatment of diarrhea and malaria [34]; and a second study found no impact of SQ-LNS on AM prevalence or WLZ [35]. In the Mali companion study to our Burkina Faso evaluation, SQ-LNS was responsible for a 29% reduction in AM incidence, mostly during the peak of AM observed between 6 and 12 months of age, with an SQ-LNS coverage of 60%–70% at that age [8]. In our study, fewer than half of the caregivers of children older than 6 months reported receiving SQ-LNS in the past month (47%, cross-sectional study; 37%, longitudinal study), and thus, it is possible that for the majority of children, the SQ-LNS did not make a large enough contribution to the nutrient adequacy of their diet to prevent AM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are, however, numerous difficulties in achieving satisfactory program effectiveness in community-based management of uncomplicated severe acute malnutrition. In the accompanying Special Issue, a number of the reported research studies illustrate some of these practical problems [15,16].…”
mentioning
confidence: 99%